(untitled) (Conferencea, 2025)
Ferdinand de Saussure defines certain relations in language that clarify the function and meaning of words as paradigmatic (associative) and syntagmatic. Paradigmatic connections combine words according to the proximity of meaning into the so-called lexical-semantic groups or semantic fields. Syntagmatic connections in the language are manifested in the combination of words.